Impact of patients' judgment skills on asthma self-management: a pilot study - Ana Maria Moreno Londoño; Peter J. Schulz (SAGE Publishing, 2014)
Background. The majority of current health literacy tools assess functional skills including reading, writing, and numeracy. Although these tools have been able to underline the impact of such skills on individuals' health behaviour, there is a need for comprehensive measures to examine more advanced skills. The individual's ability to use health-related information considering his/her own health context, and judging positive and negative consequences of their decisions has been conceptualized as judgment skills. The present study used a newly developed judgment skills tool to explore asthma self-management practices. Design and methods. Eighty asthma patients were recruited from medical offices during the year 2013. The questionnaire was self-administered and contained health literacy questions, the judgment skill tool, the Asthma Control Test, and several self-management questions. Results. Sixty-nine percent of participants had adequate health literacy, while 24% and 5% had marginal and inadequate levels, respectively. The high-judgment group referred more to their doctor when experiencing asthma problems t(76)=−2.18, P<0.032; complied more with the use of their control medicine t(77)=−3.24, P<0.002 and went more regularly to the doctor t(78)=−1.80, P<0.038 (one-tailed) than the low-judgment group. Conclusions. The judgment skills tool can help identify asthma patients' health information use and reveal how this use may affect some self-management practices.